Relationship of nutritional status and triglycerides/c-HDL ratio in adolescents cared for in a public hospital - Cachay Barboza, Edwar Paul (2020)
Objective. To determine the relationship between nutritional status according to body mass index (BMI) and triglyceride index/c-HDL in adolescents treated in a public hospital. Materials and methods. Observational, transversal, and retrospective study of the nutritional education database program of Hospital I - Rioja - EsSalud, from March 2017 to June 2018. The nutritional status was determined according to the body mass index for age (BMI/age) and the index of Tg/c-HDL as the ratio between triglycerides and HDL cholesterol. Results. The study was made up of 130 adolescents (70 females and 60 males) between 10 - 18 years old, who were treated in the nutrition service of Hospital I – Rioja- EsSalud. The average age of the adolescents was 12.6 ± 2.2 years. The average Tg/c-HDL index was 2.41 ± 0.48; it was higher in males (2.46 ± 0.51) than in females (2.37 ± 0.44); likewise, obesity (2.70 ± 0.49), overweight (2.46 ± 0.41) and the risk of underweight (2.36 ± 0.55) were the nutritional states that presented the highest Tg/c-HDL index. A positive and significant correlation (r=0.447, p=0.000) was found between BMI and Tg/c-HDL index. Conclusions. There was a positive and statistically significant relationship between the body mass index and the Tg / HDL-c index in this adolescent population. The Tg / HDL-c index was higher in the nutritional status of obesity and overweight, exceeding the value of the media population.